M1 Macrophage and M1/M2 ratio defined by transcriptomic signatures resemble only part of their conventional clinical characteristics in breast cancer - Oshi, Masanori (Sci Rep, 2020)
Tumor associated macrophages (TAMs) play a critical role in biology of various cancers, including breast cancer. In the current study, we defined “M1” macrophage and “M1”/“M2” ratio by transcriptomic signatures using xCell. We investigated the association between high level of “M1” macrophage or “M1”/“M2” ratio and the tumor immune microenvironment by analyzing the transcriptome of publicly available cohorts, TCGA and METABRIC. We found that “M1” high tumors were not associated with prolonged survival compared with “M1” low tumors, or with the response to neoadjuvant chemotherapy. “M1” high tumors were associated with clinically aggressive features and “M1” high tumors enriched the cell proliferation and cell cycle related gene sets in GSEA. At the same time, “M1” high tumors were associated with high immune activity and favorable tumor immune microenvironment, as well as high expression of immune check point molecules. Strikingly, all these results were mirrored in “M1”/“M2” ratio high tumors. In conclusion, transcriptomically defined “M1” or “M1”/“M2” high tumors were associated with aggressive cancer biology and favorable tumor immune microenvironment but not with survival benefit, which resembled only part of their conventional clinical characteristics.